Very low-temperature growth of silicon thin films using chlorinated precursors and optical properties. (15th March 2020) - Linares, Javitt; López-Suárez, A.; Ramos, C.; Picquart, M.; García-Sánchez, M.F.; Dutt, A.; Santana, G.
Abstract: In this work, the effect of the very low substrate temperature and hydrogen dilution on chemical, structural, and optical properties of polymorphous silicon thin films (pm-Si:H) using dichlorosilane as a silicon gas precursor in the plasma enhanced chemical vapor deposition (PECVD) was analyzed. The films were synthesized at a lower deposition temperature in the range from 60 to 150 °C and two H2 dilutions of 60 and 100 sccm. Hydrogen incorporation in silicon thin films has been studied by Elastic Recoil Detection Analysis (ERDA) and Fourier Transform Infrared Spectroscopy (FTIR). FTIR was also used to verify the chemical stability of the material as a function of oxidation state and hydrogen effusion. The ERDA analysis evidenced that the hydrogen content typically does not exceed 30 at. %, and the lowest value obtained is around 10 at. %. With Raman spectroscopy, the crystalline fraction was obtained in the range of 5–20%, and the average size of the embedded nanocrystals was found to be between 2 and 3 nm, which was cross-checked by High-Resolution Transmission Electron Microscopy (HRTEM). Finally, by UV–Vis spectroscopy, the effective optical band gap of this material has been calculated, and the value was found to be around 1.6 eV (absorber layer) for the samples with 100 sccm of H2 dilution and around 2.2 eV (window layer) for the samples with 60 sccm of H2 dilution. Overall the increase in the substrate temperature resulted a better ordering in the amorphous matrix, whereas, with the increase in the hydrogen dilution an improvement in the structure factor was observed. Suitable properties of the deposited material in the present work could be useful for the development of a thin silicon layer for different silicon solar cell technologies.